IMPLEMENTASI E-COURT PERMA No. 1 TAHUN 2019 TENTANG ADMINISTRASI PERKARA DAN PERSIDANGAN SECARA ELEKTRONIK DI PENGADILAN TATA USAHA NEGARA KOTA MAKASSAR - Muhammad Rifhai; Aliya Rahayu; Suci Rahmadhaniasi Putri; Ayu Larasati; Muh Ilham (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The implementation of E-Court based on Supreme Court Regulation (PERMA) No. 1 of 2019 regarding electronic case administration and trials at the Administrative Court of Makassar. Master's thesis in Public Administration program, supervised by Dr. Dandan Haryono, S.Sos., M.Si. This research on the implementation of E-Court aims to provide insights and understanding to stakeholders in the development of electronic systems, which are expected to foster superior human resources who are well-versed in the Industrial Revolution 4.0. This study employs a qualitative descriptive approach, using data collection techniques such as interviews, observations, and documentation. The findings reveal that the implementation of E-Court is a form of industrial reform requiring individuals to embrace technology. E-Court serves as an electronic platform to facilitate judicial processes at the Administrative Court. This innovation is seen as a tool for providing better services, realizing the principles of swift, simple, and low-cost services. The policy targets are expected to benefit from the simplification of all processes carried out through E-Court at the Administrative Court of Makassar.